2019
DOI: 10.1016/j.fuproc.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Co-gasification of beech-wood and polyethylene in a fluidized-bed reactor

Abstract: The co-gasification of beech-wood and polyethylene has been investigated in a lab-scale fluidised-bed reactor in the presence of four different types of bed materials (silica sand, olivine, Na-Y zeolite and ZSM-5 zeolite). ZSM-5 zeolite is very effective as a catalytic bed material in fluidized-bed reactor for wood-only gasification and cogasification in terms of high hydrogen production and CGE. Na-Y zeolite is more effective compared with ZSM-5 zeolite in co-gasification of the beech-wood and polyethylene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…When reforming is envisaged as a downstream tar upgrading unit after gasification, the most interesting temperature interval for atmospheric reforming is between 600 and 900 • C, since the gasification effluent temperature will normally be lower than 900 • C [33]. Research also suggested that high temperature might reduce H 2 yield as the reverse water-gas shift reaction is favoured due to its endothermic nature [34][35][36]. The experiments were conducted at different temperatures to investigate the most suitable conditions for toluene conversion and H 2 production.…”
Section: Influence Of Temperature On Toluene Steam Reformingmentioning
confidence: 99%
“…When reforming is envisaged as a downstream tar upgrading unit after gasification, the most interesting temperature interval for atmospheric reforming is between 600 and 900 • C, since the gasification effluent temperature will normally be lower than 900 • C [33]. Research also suggested that high temperature might reduce H 2 yield as the reverse water-gas shift reaction is favoured due to its endothermic nature [34][35][36]. The experiments were conducted at different temperatures to investigate the most suitable conditions for toluene conversion and H 2 production.…”
Section: Influence Of Temperature On Toluene Steam Reformingmentioning
confidence: 99%
“…One of the major indicators for why very little biomass waste is used in comparison to other renewable technologies is the ash constituents present in the waste feedstock. This is variable depending on the type of lignocellulosic biomass waste used; wood based examples include pine, eucalyptus, oak, poplar, beech wood, , or olive kernel wood . Other nonwood includes herbaceous wastes such as wheat straw, sugar cane straw, switchgrass, and bagasse …”
Section: Introductionmentioning
confidence: 99%
“…In order to inhibit the phenomena of bed particle agglomeration, which leads to defluidisation of the bed, BFB reactors should operate at temperatures lower than the fuel's ash melting temperature (Samiran et al, 2016). Zhu et al (2019) studied the co-gasification of polyethylene and beech wood in a lab-scale fluidised bed reactor. In particular, they investigated the effect of steam injection, feedstock composition and bed material on the hydrogen production.…”
Section: Bubbling Fluidised Bed Reactormentioning
confidence: 99%